Retinal control of lens-induced astigmatism in chicks. (May 2020) - Popa, Anca-Vanessa; Kee, Chea-Su; Stell, William K.
Abstract: Purpose: Astigmatism is a refractive error due to meridional differences in refractive powers of lens or cornea. The resulting failure to focus image points in a single plane causes blurred vision at all distances. In this study, using an animal model of lens-induced astigmatism, we tested the hypothesis that induced astigmatism is due to processing of astigmatic retinal image information by the brain, which causes distorted growth in the anterior segment via centrifugal neural projections. Methods: To induce astigmatism, +4.00DS/-8.00DC crossed-cylinder-lens goggles were affixed over the right eyes of 7-day-old chicks (P7), with the -8.00DC axis oriented vertically (at 90°) or horizontally (180°) (n = 12 each); the left eyes were without goggles (non-goggled). For all experiments, refractive errors of both eyes were measured by streak retinoscopy, before and after 1 week of lens wear. To test whether neuronal pathways between retina and brain are required, axonal conduction within the eye was blocked by intravitreal injections of tetrodotoxin (TTX; 7 μL of 10 - 4 M) in phosphate-buffered saline (PBS), or of PBS alone (7 μL); fellow open eyes received PBS alone. Pupillary light reflex (PLR) and optokinetic response (OKR) were measured, to assess the efficacy and duration of TTX action. To test whether retinal circuitry is required, groups of chicks (n = 12 each) were treated at P7 by intravitreal injection of 20 μL of mixed excitotoxins (2 μmol N-methyl-D-aspartate, 0.2 μmol quisqualic acid, 0.2 μmol kainic acid; in water) into goggled or non-goggled eyes, to compromise retinal circuitry needed for emmetropization. Results: Crossed-cylinder goggles reliably induced refractive astigmatism. Maximum astigmatic error was induced when the cylindrical axis was oriented at 90° (vertically). TTX effectively blocked nerve conduction within the eye for 48 h after injection. Goggled eyes developed astigmatism after treatment with TTX or PBS, but not after excitotoxins. Conclusion: Our hypothesis was rejected. In this model, the compensatory astigmatism induced by crossed-cylinder lenses is intrinsic to the eye, and mediated by visual processing in the retina. Highlights: Crossed-cylinder lenses induced compensatory refractive astigmatism in chicks. This effect was prevented by excitotoxins, which disrupt retinal image-processing. This effect was not prevented by tetrodotoxin block of nerve conduction in the eye. Lens-induced astigmatism in chicks is mediated by local signaling within the retina.